Complexation between the Antioxidant Pterostilbene and Derivatized Cyclodextrins in the Solid State and in Aqueous Solution - Laura Catenacci; Alexios I. Vicatos; Milena Sorrenti; Cesarina Edmonds-Smith; Maria Cristina Bonferoni; Mino R. Caira (MDPI AG, 2023)
Inadequate aqueous solubilities of bioactive compounds hinder their ability to be developed for medicinal applications. The potent antioxidant pterostilbene (PTB) is a case in point. The aim of this study was to use a series of modified water-soluble cyclodextrins (CDs), namely, hydroxypropyl β-CD (HPβCD), dimethylated β-CD (DIMEB), randomly methylated β-CD (RAMEB), and sulfobutyl ether β-CD sodium salt (SBECD) to prepare inclusion complexes of PTB via various solid, semi-solid, and solution-based treatments. Putative CD-PTB products generated by solid-state co-grinding, kneading, irradiation with microwaves, and the evaporative treatment of CD-PTB solutions were considered to have potential for future applications. Primary analytical methods for examining CD-PTB products included differential scanning calorimetry and Fourier transform infrared spectroscopy to detect the occurrence of binary complex formation. Phase solubility analysis was used to probe CD-PTB complexation in an aqueous solution. Complexation was evident in both the solid-state and in solution. Complex association constants (K1:1) in an aqueous solution spanned the approximate range of 15,000 to 55,000 M−1; the values increased with the CDs in the order HPβCD < DIMEB < RAMEB < SBECD. Significant PTB solubility enhancement factors were recorded at 100 mM CD concentrations, the most accurately determined values being in the range 700-fold to 1250-fold.